Environmentally Friendly Manufacturing of Food Additives and Functional Ingredients - Lu, Fuping; Sui, Wenjie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint focuses on fundamental and applied research on environmentally friendly manufacturing of food additives and its effect on the structural features and functional applications of functional ingredients in several fields. Food additives and functional ingredients are naturally or artificially synthesized substances that are added to foodstuﬀs to improve their color, aroma, and taste, as well as to meet anti-corrosion and other technological purposes. The innovation of clean production, encompassing environmental and sustainability issues in the manufacturing process of food additives and functional ingredients is of particular interest. Special attention is given to their bioconversion, extraction, separation and purification, stabilization, formulation and compounding, etc., as well as relevant process intensification and integration.